Risk Factors for the Onset of Aspiration Pneumonia in Stroke Patients: Risk Factors for Aspiration Pneumonia in Stroke Patients - Umam, Shah; Hassan, Naveed Ul; Ullah, Irfan; Haroon, Mohammad; Shahzad, Amjad; Khan, Ejaz; Khan, Osama Ali (Pakistan Journal of Health Sciences, 2026)
The third causes disability and is the second most common cause of death in the world. It is an interruption in the flow of blood to the brain and denies the brain tissues oxygen and other vital nutrients, thus causing ischemic damage. Objective: To determine the risk factors associated with the onset of aspiration pneumonia in stroke patients. Methods: A cross-sectional study was carried out from December 2, 2023, to May 1, 2024, at the Department of Medicine, Khyber Teaching Hospital. Participants included 149 patients aged ≥18 years who had been diagnosed with aspiration pneumonia complicating a stroke. The following risk variables for aspiration pneumonia were investigated: diabetes, smoking, age over 65, stroke type, Glasgow Coma Scale (GCS) <8, and nasogastric (NG) feeding. Data analysis was done with SPSS version 25.0. Results: The patients’ average age was 61.77 ± 9.58 years. The most frequent risk factor seen in 101 individuals (71.8%) was the kind of ischemic stroke, which was followed by the lack of NG feeding in 95 patients (63.8%). The least prevalent factor was diabetes mellitus (n=66, 44.3%). Conclusions: Aspiration pneumonia is a dreadful complication in stroke patients. It is more frequent in patients with advanced age, with a GCS less than 8, and without NG feeding.